2002
DOI: 10.1164/rccm.200204-363oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung Deposition and Efficiency of Nebulized Amikacin duringEscherichia coliPneumonia in Ventilated Piglets

Abstract: Lung tissue deposition and antibacterial efficiency of nebulized and intravenous amikacin (AMK) were compared in anesthetized and ventilated piglets suffering from a bronchopneumonia produced by the intrabronchial inoculation of Escherichia coli. AMK was administered 24 hours after the inoculation either through an ultrasonic nebulizer (45 mg x kg-1, n = 10) or by intravenous infusion (15 mg x kg-1, n = 8). Piglets were killed 1 hour after a second AMK administration performed 24 hours after the first one, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
137
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(146 citation statements)
references
References 35 publications
4
137
1
4
Order By: Relevance
“…In this study, Lu et al demonstrated that, in areas of severe pneumonia, lower drug concentration occurred with inhaled colistin compared with areas with mild pneumonia; these observations echoed results of prior studies using aminoglycosides [12]. However, despite lung tissue concentrations influenced by severity of lung lesions, inhaled colistin was associated with comparable bacterial clearance in lung segments with mild and severe Intensive Care Med (2010) 36:1110-1111 DOI 10.1007/s00134-010-1883-8 EDITORIAL Pseudomonas pneumonia [11].…”
supporting
confidence: 82%
“…In this study, Lu et al demonstrated that, in areas of severe pneumonia, lower drug concentration occurred with inhaled colistin compared with areas with mild pneumonia; these observations echoed results of prior studies using aminoglycosides [12]. However, despite lung tissue concentrations influenced by severity of lung lesions, inhaled colistin was associated with comparable bacterial clearance in lung segments with mild and severe Intensive Care Med (2010) 36:1110-1111 DOI 10.1007/s00134-010-1883-8 EDITORIAL Pseudomonas pneumonia [11].…”
supporting
confidence: 82%
“…This model closely resembles human pneumonia and has proven to be very useful for evaluating different aspects related to the diagnosis and treatment of severe pneumonia [21][22][23][24][25][26][27]. Using this animal model, severe pneumonia was reproduced and the associated inflammatory response was studied after inoculation with high concentrations of Pseudomonas aeruginosa [28], the most lethal causative microorganism, both in CAP and ventilator-associated pneumonia [2,8,29].…”
mentioning
confidence: 99%
“…MARQUETTE et al [7] have developed an animal model of pneumonia in mechanically ventilated piglets that closely resembles severe human pneumonia. This model has proved to be very useful for the proper evaluation of different aspects regarding diagnosis and treatment [8][9][10][11][12][13]. Pseudomonas aeruginosa is one of the most lethal causative microorganisms both in communityacquired pneumonia and ventilator-acquired pneumonia [1,2,6].…”
mentioning
confidence: 99%